STUDI LITERATUR: PERAN MODEL PEMBELAJARAN INKUIRI DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Jihan Nabilatus Sholihah; Rayendra Wahyu Bachtiar; Firdha Yusmar; Fauziyatul Iffah; Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Junior high school students' critical thinking skills need to be possessed and trained to face the 21st century. The increasingly developing era of education is an important aspect to combat the future. However, junior high school science learning is generally still relatively low because the learning approach does not involve students enough. One learning model that is considered effective is inquiry learning. This learning model involves students and encourages them to improve their critical thinking skills. This study aims to examine the role and influence of the inquiry learning model to improve the critical thinking skills of junior high school students. The method used is the Systematic Literature Review (SLR) from Google Scholar. The data search keywords are inquiry learning and critical thinking skills, 20 articles were found and 10 articles will be reviewed with these criteria. The research findings show that the use of the inquiry learning model can improve the thinking skills of junior high school students in science subjects.